2020
DOI: 10.1007/s12186-020-09242-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards successful innovations in education: Development and validation of a multi-dimensional Innovative Work Behaviour Instrument

Abstract: Our study aims to develop and validate a multidimensional Innovative Work Behaviour instrument to measure teachers IWB. Current IWB conceptualizations and operationalizations need further attention. Existing measurements miss empirical evidence of the construct validity and moreover do not include a sustainability dimension. Based on a thorough and comprehensive conceptualization of IWB, we first adapted and extended the items of previously used instruments and developed items for a sustainability dimension. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 45 publications
3
49
0
3
Order By: Relevance
“…This was measured with the 44‐item IWB Instrument developed by Lambriex‐Schmitz et al . (2020), measuring five dimensions of IWB: Opportunity Exploration, Idea Generation, Idea Promotion, Idea Realization (criterion‐based implementation and learning‐based communication) and Idea Sustainability (internal embedding and external dissemination). The items were scored on a six‐point Likert‐scale, ranging from 1 (=strongly disagree) to 6 (=strongly agree), and analysed in the Rasch rating scale model (Rasch, 1960).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was measured with the 44‐item IWB Instrument developed by Lambriex‐Schmitz et al . (2020), measuring five dimensions of IWB: Opportunity Exploration, Idea Generation, Idea Promotion, Idea Realization (criterion‐based implementation and learning‐based communication) and Idea Sustainability (internal embedding and external dissemination). The items were scored on a six‐point Likert‐scale, ranging from 1 (=strongly disagree) to 6 (=strongly agree), and analysed in the Rasch rating scale model (Rasch, 1960).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, building further on Janssen (2000) and, Messmann and Mulder (2012), we extended the operationalization of IWB including a sustainability dimension (Lambriex‐Schmitz et al ., 2020) to address the problem of superficial innovation and to assure durable implementation. This leads to a broader definition of IWB, namely as a multi‐stage iterative process (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ensuring that the education system remains relevant and in line with the moving times is one of the main challenges to be faced in a rapidly changing open environment and, as such, the education system cannot be static, but rather be dynamic and continually changes to fulfil the aspirations and needs to be at par and relevant with current developments. Additionally, the creation of innovation in the education field depends on teachers’ innovative behaviour [ 22 , 23 , 24 , 25 ]; therefore, it is important to equip teachers with this type of behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated that team learning behaviours, especially team reflectivity and boundary, relate positively to IWB among vocational educators (Widmann & Mulder, 2018). Further research established and validated a multidimensional Innovative Work Behavior Instrument for IWB Teacher Measurement (Lambriex-Schmitz et al, 2020). Lambriex-Schmitz et al (2020) also found that management support and exposure to innovations served as a predictor for teachers' IWB.…”
Section: Introductionmentioning
confidence: 97%
“…Further research established and validated a multidimensional Innovative Work Behavior Instrument for IWB Teacher Measurement (Lambriex-Schmitz et al, 2020). Lambriex-Schmitz et al (2020) also found that management support and exposure to innovations served as a predictor for teachers' IWB. A previous study focusing on Malaysia identified the level of IWB among secondary school teachers in Malaysia and the impact of transformational leadership on IWB teachers before and after the inclusion of teaching commitment as a mediator (Aziz et al 2020;Ismail & Mydin, 2019).…”
Section: Introductionmentioning
confidence: 98%